Design and evaluation of Pulsatile drug delivery of Losartan Potassium - Ashwini, MS; Ahmed, Mohammed Gulzar (Dhaka University Journal of Pharmaceutical Sciences, 2014)
The study was designed for the investigation of pulsatile device to achieve time or site specific release of Losartan potassium based on chronopharmaceutical considerations. The basic design involves the preparation of cross linked hard gelatin capsules by using formaldehyde, then the drug diluent mixture were prepared and loaded in, which was separated by using hydrogel plugs of different polymers of different viscosities. Prepared formulations were subjected to evaluation of various parameters like weight variation, percentage drug content, in vitro drug release and stability studies. Weight variation and percentage drug content results showed that they were within the limits of official standards. The in-vitro release studies revealed that the capsules plugged with polymer HPMC showed better pulsatile or sustained release property as compared to the other formulations. The stability studies were carried out for all the formulations and formulations F1 & F2 were found to be stable. Dhaka Univ. J. Pharm. Sci. 12(2): 119-123, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17610